Development and Research of Ion Optics Digital Simulation System for EI Source - Li-na YANG; Xing-chuang XIONG; Zi-long LIU; Xiang FANG (Zhipu Xuebao)
The ion optical system is an important component of electron impact (EI) ion source, which uses electrostatic lens to extract ions in the ion chamber, further focus, accelerate and shape, and regulate the speed and energy of the ion beam. The performance of the ion optical system will directly affect the sensitivity and stability of the mass spectrometer. Based on the digital simulation, the ion optical system of EI source can be used to track the movement trajectory of ions from generation to the moment before entering the mass analyzer, which is helpful to deeply understand and recognize the dynamic behavior of ions in the system, and study the key influencing factors of ion movement. In this paper, the ion optical digital simulation system of EI source named Sim-EI-Lens-COM-V1.0 was developed. The geometric structure of each component in the simulation system can be uniformly configured and modified, which is suitable for the simulation of different types of ion optical systems. Based on the developed simulation system, two kinds of typical ion optics with cylindrical and sheet lenses were constructed. The key factors affecting the ion transport efficiency, such as geometric size and voltage parameter of each component in the simulation system, the species and total number of ions produced, and the time of the ion to pass through the system, were studied. Firstly, the influences of the electrostatic lens thickness on the ion dynamic behavior and transport efficiency were investigated. Then appropriate number and initial distribution of ions were selected, and the parametric scanning calculations of the voltage parameters were carried out. Through coarse, fine and precise adjustment of different voltage step values, the optimal voltage combinations of two typical ion optics systems were achieved. The performances of the two ion optical systems were compared under the optimal voltage combination. The result showed that the ion transmission in cylindrical lens ion optical system can reach to 97%, and it can reach more than 99% in sheet lens. The time for ions to pass through the system increases with the increasing of ion mass-charge ratio. The time to pass through the cylindrical lens is shorter than that of the sheet lens under the same ion mass-charge ratio. The radial energy distributions of ions at the outlet of the two ions optical systems are similar, and the axial energy distribution at the outlet of the sheet lens is more concentrated with higher consistency.